SYNDROME OF REGURGITATION AND VOMIT AMONG CHILDREN AND ITS NUTRITIONAL CORRECTION - T.S. Lazareva; A.A. Zhil'tsova (Вопросы современной педиатрии, 2007)
The lecture is dedicated to one of the most frequently met troubles children face — regurgitation. The article highlights the reasons, leading to regurgitation and their noncdrug correction. The authors show general characteristics of antireflux formulas. Apart from that, they describe the principles of prescription and application of formulas with different thickeners.Key words: infants, regurgitation, formula, correction, diet.